Carbon Nanodots: Supramolecular Electron Donor-Acceptor Hybrids Featuring Perylenediimides - Strauß, Volker; Margraf, Johannes; Dirian, Konstantin; Syrgiannis, Zois; Prato, Maurizio; Wessendorf, Cordula; Hirsch, Andreas; Clark, Timothy; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2015)
We describe the formation of charge-transfer complexes that feature electron-donating carbon nanodots (CND) and electron-accepting perylenediimides (PDI). The functionalities of PDIs have been selected to complement those of CNDs in terms of electrostatic and -stacking interactions based on oppositely charged ionic head groups and extended -systems, respectively. Importantly, the contributions from electrostatic interactions were confirmed in reference experiments, in which stronger interactions were found for PDIs that feature positively rather than negatively charged head groups. The electronic interactions between the components in the ground and excited state were characterized in complementary absorption and fluorescence titration assays that suggest charge-transfer interactions in both states with binding constants on the order of 8x10(4)M(-1) (25Lg(-1)). Selective excitation of the two components in ultrafast pump probe experiments gave a 210ps lived charge-separated state.
Keywords: carbon nanodots; charge transfer; donor-acceptor compounds; perylenediimides; transient absorption